Perbandingan Nilai Perjuangan pada Tokoh-Tokoh Novel Sang Pemimpi dan Negeri 5 Menara - Ningrum, Arfia Sulistya; Chanafiah, Yayah; Hiasa, Fina (Jurnal Korpus, 2025)
The aim of this research is to describe the comparison and message of the values ​​of struggle of the characters in the novels Sang Pempian and Negeri 5 Menara. This research uses a qualitative method, a comparative literary approach. The results of the comparison show that the two novels have similarities, namely that they both show the values ​​of struggle, hard work, enthusiasm and never giving up, willingness to sacrifice, cooperation, mutual respect, solidarity, piety and trust, courage and optimism in achieving goals. However, the struggle is carried out in a different context. In the novel Sang Pemimpi is driven by low economic conditions so that apart from carrying out their study duties as students, the characters also have to work to pay for school. Meanwhile, within Negeri 5 Menara the focus of struggle is in the context of learning where a heavy portion is to develop oneself in Islamic boarding schools where the rules are strict. The messages that can be learned are daring to dream big, fighting above average, prayer and trust, helping each other, the importance of pursuing education, teachers as role models, and the importance of support from those around you.